BUKAN SEKEDAR KERINGAT: ALASAN CRC JAMBI MENJADI LOKASI FAVORIT MAHASISWA UNTUK BEROLAHRAGA - Toto Yuwanto; Heru Darmawan; Dimas Fajar Yoandani; Rahul Illahi; Mohd Adrizal; Ely Yuliawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical activity plays an essential role in maintaining the physical and mental well-being of university students. The selection of an appropriate sports facility is one of the factors that influences individuals' motivation to engage in regular physical activity. CRC Jambi has become one of the most popular sports venues among university students. This study aimed to analyze the factors influencing students' preference for CRC Jambi as their favorite place for exercise. A descriptive quantitative approach was employed using purposive sampling. Data were collected through a questionnaire distributed to university students who had previously exercised at CRC Jambi and were analyzed using descriptive statistics in the form of percentages. The findings revealed that accessibility was the primary factor influencing students' preference (100% positive responses), followed by environmental comfort (94.7%), a supportive environment for physical activity (84.2%), CRC Jambi as the preferred exercise location (78.9%), and the availability of sports facilities (57.9%). These findings indicate that students prioritize accessibility, comfort, and environmental quality over the completeness of sports facilities when choosing a place to exercise. Therefore, CRC Jambi serves not only as a venue for physical activity but also as a space that promotes a healthy lifestyle and facilitates social interaction among university students.